SHARIA EMPLOYEE COOPERATIVE SERVICE SYSTEM PT. PUPUK ISKANDAR MUDA - Hayati, Nurul; Izza, Nurul; Rahmadani, Zuhra; Fajiral, Raihan; Sinta, Irada (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This study aims to formulate the problem "how is the service system in the Islamic employee cooperative PT. PIM?" The determination is based on direct interviews with resource persons, members and employees of the PT.PIM sharia employee cooperative Proportional Stratified Sample Random Sampling. The method used is an explanatory survey method. With using primary and secondary data. The variables analyzed are the service quality factors of cooperatives and Cooperative benefit variable. While testing the validity of the correlation technique used through the Correlation Coefficient Product Moments from Pearson. The reliability test used is the split-half correlation technique with the Spearman-Brown formula. While data analysis techniques, used correlation analysis and regression analysis multiple, the results of this study are useful for implementing the quality of useful services provided by cooperatives, so member participation is also increasing